Evaluation of a Residential Nutrition Rehabilitation Center in Rural Bolivia: Short-Term Effectiveness and Follow-Up Results. (June 2014) - Forney, Kristen M.; Polansky, Lauren S.; Rebolledo, Paulina A.; Huamani, Katherine Foy; Mues, Katherine E.; Ramakrishnan, Usha; Leon, Juan S.
Background: Nutrition rehabilitation centers (NRCs) have shown mixed results in reducing morbidity and mortality among undernourished children in the developing world. Follow-up on children after leaving these programs remains undocumented. Objective: To assess the nutritional improvement of children attending the Centro de Rehabilitación Infantil Nutricional (CRIN), a residential NRC in rural Bolivia, from entrance to exit and to a household follow-up visit 1 month to 6 years later, and to identify factors associated with nutritional improvement. Methods: A retrospective analysis was conducted of clinical records collected by CRIN staff from 135 children under 3 years of age attending CRIN in rural Cochabamba, Bolivia, from 2003 to 2009, and of clinical records of household follow-up measurements on a subset of 26 children that were taken between 1 month and 6 years postexit. Nutritional status was evaluated by calculating z-scores for weight-for-height (WHZ), weight-for-age (WAZ), and height-for-age (HAZ). Children with z-scores < −2 were considered to be wasted, underweight, or stunted, respectively. Results: The prevalence of wasting decreased significantly, while the prevalence of stunting did not change significantly between entrance and exit from the program. From entrance to exit, the mean changes in WHZ (0.79) and WAZ (1.08) were statistically significant, while the mean change in HAZ (–0.02) was not significant. Linear regression analysis suggested that nutritional status and diarrhea at entrance had the greatest effect on WHZ and HAZ changes between entrance and exit. Children maintained their nutritional gains from the program between exit and follow-up and showed statistically significant improvement in WAZ (but not HAZ). Conclusions: CRIN is effective at rehabilitating nutritional deficits associated with wasting, but not those associated with stunting.